Political economy and pensions in ageing societies – a note on how an "impossible" reform was implemented in Sweden - Agneta Kruse (Lund University, School of Economics and Management, Department of Economics, 2005)
Ageing puts a strain on most countries' pension systems; forecasts show them to be more or less unsustainable. Evidence from social choice research, theoretical as well as empirical, does not seem to offer a way out of the dilemma, as the median voter will resist a reform. Despite this, Sweden has implemented a major reform, supposedly making the system sustainable. The question in this paper is thus: how was it possible to launch such a reform in Sweden? The analysis is based on majority voting models. Important explanatory factors are age structure as well as the age of the median voter; both of these go against the probability of a reform. A focus on age structure in combination with transitional rules and specific features of the reform may provide an explanation.
Keywords: D72; H55; J26; 330; political economy; pension reform; median voter; age structure